Ela muda tudo o que toca e tudo o que ela toca, muda: a construção de uma nova espiritualidade a partir do corpo e das fases da vida - Alves, Sabrina (2011)
The dissertation "She changes everything She touches and everything She touches changes: the construction of a new spirituality from the body and the stages of life." is the result of a two-year research. The goal of this work was to understand spirituality and the construction of the divine that is born from the body based on biological sexual phases of women, as well as to understand the processes of resistance, the potential of this knowledge and practices, and how these individuals would be producing new religious readings based on these perceptions. As we listen and analyze the life stories of four characters who use biological passages of their bodies in order to ritualize and give birth to a new spirituality, we realize that they are breaking dichotomies and privileging the integrality of their bodies in search of a redemption from their choices. We also realize that they have been using their experiences to encourage other women to do the same in groups called "circles of women". Finally, in a processual form, these women have established a closer relationship between their body and the earth, being the last one the goddess herself.